Parallel Processing Applied to Robot Manipulator Trajectory Planning - Nomiyama, Denis Hamilton; Hirakawa, André Riyuiti; Sato, Líria Matsumoto (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
The parallel processing has been applied in real time systems which require intensive data processing. Ao application which requires high performance processing is that related to the control of the trajectory planning of a manipulator. There are several methods for conducting the trajectory planning. One of them is the Variational method. This method consists of an iteractive process for executing the calculations related to the configuration of joints of a redundant manipulator. As in every iteractive procedure, the Variational method demands high volume of processing, causing a delay that wouldn't allow a real-time system to work, and also its simulations. To solve this problem, parallel processing can be used. This paper presents a parallel processing algorithm to solve the trajectory planning problem, based on redundant manipulator joints. In this case, the Variational method is applied with the use of a parallel architecture.